Pengaruh Jumlah Uang Beredar, Inflasi dan Kurs Rupiah Terhadap Margin Pembiayaan Murabahah PT. Bank Syariah Indonesia Tahun 2013-2022 - Qorry Prananda Aulia; Imsar Imsar; Muhammad Ikhsan Harahap (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This study aims to determine the influence of the Influence of Money Supply, Inflation and Rupiah Exchange Rate on Murabahah Financing Margin in Indonesia Sharia Banks throughout Indonesia from 2013-2022. The type of research conducted is quantitative research. The method used in this study used the analysis of the Vector Auto Regression model of the VECM model and a data tool processed using Eviews 10. The data used is secondary data taken through the official website of the Central Statistics Agency (BPS) for a period of 10 (ten) years from 2013-2022. Based on the results of the study, it is known that the results of the Vector Error Correction Model (VECM) test of this study show that only the variables of the Money Supply and the Rupiah Exchange Rate have a positive and significant impact, while the influence of the Inflation variable on Murabahah Financing Margin (Case Study of Bank Syariah Indonesia in 2013-2022) in the short term has a positive and insignificant impact. The Effect of Money Supply and Inflation on Murabahah Financing Margin has a positive and significant impact, while the influence of the Rupiah Exchange Rate variable on Murabahah Financing Margin in the long term has a negative and insignificant impact.